Long-chain polyunsaturated fatty acid status during pregnancy and maternal mental health in pregnancy and the postpartum period: Results from the GUSTO study - Chong, Foong Foong Mary (Physicians Postgraduate Press, 2015)
10.4088/JCP.14m09191